Additions to the decapod crustacean fauna of the Hawaiian Islands, I. A review of the genus Sakaila Manning and Holthuis, 1981 (Decapoda, Brachyura, Aethridae), with the description of a new species from the Northwestern Hawaiian Islands - Martin, Joel W.; Godwin, Scott; Moffitt, Robert (Zootaxa, 2009)
The brachyuran crab genus Sakaila, currently considered a member of the family Aethridae, is reviewed and revised. Illustrations are provided for all of the known species, and a new species, the fourth in the genus, is described based on one female from French Frigate Shoals, one male from Maro Reef, both in the Northwestern Hawaiian Islands, and a second male from Johnston Atoll. Previous species are known only from the eastern Atlantic off the west coast of Africa (S. africana Manning and Holthuis, 1981) and from the far western Pacific off Japan (S. japonica Sakai, 1963, and S. imperialis Sakai, 1963). The new species differs from its congeners mostly in the overall spination of the carapace and legs, which is more pronounced in the new species. A key to the known species is provided and the current status of each species is discussed.